Pengaruh Kompres Aloe Vera Terhadap Nyeri Pembengkakan Payudara Pada Ibu Nifas: EVIDENCE BASED CASE REPORT - Marsaa Khairani, Zakiyyah; Yanti, Yulidar; Ulfah Fatimah, Yulia (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: The postpartum is a period of adaptation where various problems arise, a problem that often arises during the postpartum period is breast engorgement. Breast engorgement occurs due to non-continuous breastfeeding so that remaining breast milk collects in the duct area. This occurs, among other things, because breast milk production increases, early breastfeeding is hampered, poor latching, less frequent expression of breast milk, and restrictions on breastfeeding time. According to the Indonesian Ministry of Health, breast engorgement often occurs in 10-20% of the population of postpartum mothers, which can make the situation worse if not treated properly. Objective: This evidence-based case report aims to determine the effect of aloe vera compresses on breast engorgement of postpartum mothers. Method: Evidence base case report (EBCR) through literature searches in several articles, namely Pubmed and Google Scholar. Results: The breasts were painful and swollen after being given treatment by applying aloe vera compresses for 20 minutes which was done 2-3 times a day for 7 days which reduced breast engorgement, seen from the decreasing Visual Analog Scale (VAS) assessment results. Conclusion: The application of non-pharmacological therapy, namely Aloe vera compress, contains anthraquinone containing aloin and emodin which can function as an analgesic so that it is effective in treating breast engorgement.